2019
DOI: 10.1111/1751-2980.12796
|View full text |Cite
|
Sign up to set email alerts
|

Artificial neural networks accurately predict intra‐abdominal infection in moderately severe and severe acute pancreatitis

Abstract: Objective: The aim of this study was to evaluate the efficacy of artificial neural networks (ANN) in predicting intra-abdominal infection in moderately severe (MASP) and severe acute pancreatitis (SAP) compared with that of a logistic regression model (LRM). Methods: Patients suffering from MSAP or SAP from July 2014 to June 2017 in three affiliated hospitals of the Army Medical University in Chongqing, China, were enrolled in this study. A univariate analysis was used to determine the different parameters … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 32 publications
0
15
0
2
Order By: Relevance
“…Several other studies using AI‐based methods reported similar results 9,11–15 . AI‐based methods could also identify specific complications of AP such as porto‐venous thrombosis with an accuracy of 83% 16 and intra‐abdominal infections with a receiver operating characteristic curve of 0.923 [0.883–0.952] 17 …”
Section: Artificial Intelligence Applications In Pancreatitismentioning
confidence: 80%
“…Several other studies using AI‐based methods reported similar results 9,11–15 . AI‐based methods could also identify specific complications of AP such as porto‐venous thrombosis with an accuracy of 83% 16 and intra‐abdominal infections with a receiver operating characteristic curve of 0.923 [0.883–0.952] 17 …”
Section: Artificial Intelligence Applications In Pancreatitismentioning
confidence: 80%
“…As a result, several potentially important factors may have been excluded prior to the ANN modeling. Therefore, due to the complex learning processes involved in the model development, it may be impossible to figure out what parameters exist in the hidden layers (the so-called black box) or to reproduce the same ANN model ( 12 , 18 ). Although the dropout method was applied to avoid bias and overfitting, and our network was validated for stability, there is risk when applying this network to a larger data set from multiple institutions ( 25 ).…”
Section: Discussionmentioning
confidence: 99%
“…The artificial neural network (ANN) is a non-linear regression model and can be used in a computer-aided diagnosis system ( 12 ). An ANN model based on a combination of non-invasive clinical parameters from BA patients and their differential diagnosis was developed.…”
Section: Introductionmentioning
confidence: 99%
“…Three studies aimed to predict complications by using an ANN and compared it to logistic regression (LR) modeling. The results showed that the ANN significantly outperformed the LR modeling in predicting the occurrence of several complications during the course of the disease in all three studies 17–19 . Two studies reported ANNs that predict multi‐organ failure (MOF) in AP patients based on clinical and laboratory findings.…”
Section: Pancreatitismentioning
confidence: 97%
“…Several studies report ANNs that predict complications and mortality in patients with AP with high accuracy, ranging from 83.0% to 97.5% 17–23 . Three studies aimed to predict complications by using an ANN and compared it to logistic regression (LR) modeling.…”
Section: Pancreatitismentioning
confidence: 99%